Comparación de dos técnicas para la obtención de complejos cumulus ovocito porcinos - Lorenzo, M.S. (2015)
The selection of high quality oocytes is a key for the succeeding of in vitro embryo production. The oocyte collection techniques would be related to its quality. The aim of this study was to compare two different porcine cumulus oocyte complexes (COCs) collection methods: slicing and follicular aspiration. The rate of nuclear maturation and early and late apoptosis in COCs were measured. By using follicular aspiration, significantly higher percentages in the oocyte nuclear maturation were obtained. However this technique was restricted to large antral follicles and allowed to recover lower amounts of oocytes per ovary than the slicing method. In addition, apoptosis in porcine COCs would not be related to the collection methods used.